PARADIGMA MAKNA FINAL DAN MENGIKAT PUTUSAN DEWAN KEHORMATAN PENYELENGGARA PEMILU - Ismail, Ismail; Hapsoro, Fakhris Lutfianto (Penerbit Universitas Atma Jaya Yogyakarta, 2021)
In several cases of settlement of the State Administrative Court, the Panel of Judges annulled the Presidential Decree (beschikking) which followed up on a Decision of the Honorary Council of Election Organizers regarding the dishonorable dismissal of members of the General Election Commission. Basically, the decision of the Honorary Election Organizing Council is final and binding. With this practice in mind, this paper discusses how the paradigm is